2001
DOI: 10.1053/jlts.2001.22455
|View full text |Cite
|
Sign up to set email alerts
|

Use of daclizumab as initial immunosuppression in liver transplant recipients with impaired renal function

Abstract: The addition of daclizumab (a human immunoglobulin G1 monoclonal antibody that blocks interleukin-2 receptors on T lymphocytes) to mycophenolate mofetil (MMF) and steroids is a new option for initial immunosuppression in patients undergoing liver transplantation (LT) with impaired renal function. We evaluated the efficacy and safety of daclizumab in preventing rejection in 25 patients with impaired kidney function undergoing LT. Patients with serum creatinine (Cr) levels greater than 2 mg/dL immediately before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 24 publications
2
36
0
1
Order By: Relevance
“…18 Although delaying initiation of CNI with interleukin-2 receptor (IL-2R) antagonists basiliximab and daclizumab has been associated with acceptable short-term outcomes, long-term benefits in renal function have not been observed. 16,17,20,29,30 In comparison with our current study, the lack of apparent long-term renal function benefits from the use of IL-2R antagonists to delay CNI initiation may be related to the differences in the patient populations studied and the pharmacology of these antibodies. In previous studies that used IL-2R antagonists to delay initiation of CNI, most patients did not have preexisting renal dysfunction and were not critically ill. 16,19,29 In this study, all patients had preexisting renal dysfunction (Ն1.5 mg/dL), and most were critically ill at the time of transplant, as evident by the high MELD score and high percentage of patients hospitalized prior to transplant.…”
Section: Discussionmentioning
confidence: 52%
“…18 Although delaying initiation of CNI with interleukin-2 receptor (IL-2R) antagonists basiliximab and daclizumab has been associated with acceptable short-term outcomes, long-term benefits in renal function have not been observed. 16,17,20,29,30 In comparison with our current study, the lack of apparent long-term renal function benefits from the use of IL-2R antagonists to delay CNI initiation may be related to the differences in the patient populations studied and the pharmacology of these antibodies. In previous studies that used IL-2R antagonists to delay initiation of CNI, most patients did not have preexisting renal dysfunction and were not critically ill. 16,19,29 In this study, all patients had preexisting renal dysfunction (Ն1.5 mg/dL), and most were critically ill at the time of transplant, as evident by the high MELD score and high percentage of patients hospitalized prior to transplant.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, different dosing regimens (five doses or singleshots) have been tested in liver-transplanted patients in order to limit the use calcineurin inhibitors in the early postoperative period in patients with impaired renal function; with good success (32,33). However, daclizumab application without calcinurin inhibitors was not effective in liver transplantation (34).…”
Section: Daclizumab In Liver Transplantationmentioning
confidence: 99%
“…It is a humanized IgG1 form of murine anti-IL-2Rα mAb anti-Tac and retains the murine complementarity determining regions (CDRs) and some key residues of the framework regions (FWRs) for high specificity and high affinity [23]. Daclizumab has been successfully used in the treatment of renal transplantation [24][25][26][27][28] and liver transplantation [29][30][31][32], and is promising for the treatment of acute graft-versus-host disease [33,34], multiple sclerosis [35], and malignancies such as T cell leukemia [19]. The non-randomized large multi-center trials in phase I/II showed that the safe and efficacious dosages of basiliximab and daclizumab are quite different (basiliximab in two 20 mg/kg doses and daclizumab in five 2 mg/kg doses) [36].…”
Section: Introductionmentioning
confidence: 99%